Studi Implementasi Green Building pada Terminal Joyoboyo Surabaya - Zain Assalam, Muhammad Gilang; Paryoko, Vijar Galax Putra Jagat (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
The impact of globalization includes negative effects on the environment. With increasing awareness among the public about the alarming state of environmental health and the development of sustainable and environmentally friendly construction in Indonesia, this study aims to understand the strategies employed by Joyoboyo Terminal in obtaining green building certification from the Green Building Council Indonesia (GBCI). A qualitative method is used as the data source, with data collected through observation, interviews, and literature review. The scope of this research uses green architecture parameters, including Respect for Site, Respect for Users, Working with Climate, Conserving Energy, Minimizing New Resources, and Holism. The results of this study indicate that Joyoboyo Terminal has applied green architecture principles as an environmentally friendly terminal. This research is expected to provide references and development for subsequent studies on sustainability strategies in terminals and to raise public awareness of green architecture in buildings as an effort towards environmental friendliness and global health.